THE EFFECTIVENESS OF HOUSEKEEPING DRILLING SKILLS IN INCREASING STUDENT ADAPTABILITY IN HOSPITALITY INDUSTRY -BASED LEARNING PROGRAMS - Risman Jaya; Daniel Adolf Ohyver; Andi Ade Zulkifli (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
The hospitality industry demands professional, skilled, and adaptive human resources to meet guest needs. Vocational education in the hospitality sector needs to emphasize industry-based practical learning to prepare students to face the world of work. One method that can be used is housekeeping drilling skills, a repetition-based training that emphasizes consistency, speed, and precision in housekeeping skills. This study aims to analyze the effectiveness of the housekeeping drilling method in increasing the adaptability of the Room and Hospitality Management Division Study Program students who study Housekeeping courses at the Makassar Tourism Polytechnic. The research uses a qualitative approach with the research location at the Makassar Tourism Polytechnic, one of the vocational universities under the Ministry of Tourism of the Republic of Indonesia. Over six months, data were collected through in-depth interviews and direct observation of students who participated in housekeeping practices (April-September 2025). The analysis was conducted descriptively to understand students' experiences, perceptions, and challenges in drilling housekeeping skills. The study results show that the housekeeping drilling method improves technical skills, discipline, and students' adaptability to the dynamic hospitality work environment. Repetitive exercises strengthen the motor aspect and cognitive understanding related to industry operational standards. This study contributes to the development of a vocational curriculum. It enhances the synergy between educational institutions and the hospitality industry in producing more ready-to-use, competent, and adaptive graduates.